Elementary Students’ Attitudes towards an Online Visiting Lecture in Covid-19 School Closure Period - Aryanti Aryanti; Tommy Tanu Wijaya (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
This study aims to describe the attitudes of elementary students towards online visiting lectures and teacher problems while teaching in the Covid-19 school closure period. The visiting lecture was conducted to relieve the boredom of online learning. The novelty of online visiting lecture conducted at elementary school level in Covid-19 school closure period. This study sample comprised  48 third grade students at a private elementary school in Bandung, West Java, Indonesia. This study used a qualitative approach. The data were collected through observation and interviews with elementary school students. The results showed that the students' attitudes towards online visiting lecture in Covid-19 school closure period were very good. The students engaged in learning actively. When the visiting lecturer asked questions, the students answered the questions confidently. In conclusion, the visiting lecture can be held in Covid-19 school closure period when students need a new online learning atmosphere. In Indonesia, Covid-19 pandemic has lasted more than 1 year, and it causes boredom of online learning. Holding visiting lecture is an effective way to increase students’ learning interest and motivation so that the online teaching and learning process runs more efficiently.